The effect of submersion denture base acrylic resin in a betel leaf ekstract solution against growth candida albicans - Ardiansyah S. Pawinru; Andi Izham (Journal of Dentomaxillofacial Science, 2017)
Objective: Microorganisms are often found in the oral cavity is candida albicans approximately 40 % in the oral cavity. Candida albicans can penetrate the acrylic resin that can infect the soft tissue and is the cause of denture stomatitis therefore the disinfection pf denture base is an important factor that must be done. The purpose of the research is to determine how the effect of submersion denture base acrylic resin in a betel leaf exstract solution against growth candida albicans.Material and Methods: This research is an experimental laboratory with a longitudinal design (follow-up) study. The Sampling method used is Total Sampling. This study used a sample of 12 pieces of denture base material acrylic resin to be suspended candida albicans fungus for 1x24 hours at 37oC.Results: The number of candida albicans colonies n denture base acrylic resin which soaked betel leaf extract solution that the dilution 10-1with consentration 2.5% total colony count is 2 and the results 2.0 x 101 CFU/ml , on a control solution that the dilution 10-2 total colony 355 and the result 3.55x104 CFU/ml , that the dilutionÂ  10-3 total colony 62 and the result 6.2x104 CFU/ml.Conclusion: Betel leaf extract (piper linn) can inhibit the growth of candida albicans on denture base of acrylic resin, betel leaf extract (piper linn) 5% is a minimal anti-fungal power that can be used as a disinfectant solution in acrylic resin denture.